Diurnal Variation in Systemic Acute Inflammation and Clinical Outcomes Following Severe Blunt Trauma - Zaaqoq, Akram M.; Namas, Rami A.; Abdul-Malak, Othman; Almahmoud, Khalid; Barclay, Derek; Yin, Jinling; Zamora, Ruben; Rosengart, Matthew R.; Billiar, Timothy R.; Vodovotz, Yoram (Frontiers in Immunology, 2019)
Circadian oscillations of immunity and inflammation have been characterized, and animal studies suggest that the time of day is a determinant of the immunological response to both injury and infection. We hypothesized that due to this diurnal variation, time of injury can affect the systemic inflammatory response and outcomes post-trauma and tested this hypothesis by examining the dynamics of circulating inflammatory mediators in blunt trauma patients injured during daytime vs. nighttime. From a cohort of 472 blunt trauma survivors, two stringently matched sub-cohorts of moderately/severely injured patients [injury severity score (ISS) >20] were identified. Fifteen propensity-matched, daytime-inured (“mDay”) patients (age 43.6 ± 5.2, M/F 11/4, ISS 22.9 ± 0.7) presented during the shortest local annual period (8:00 am-5:00 pm), and 15 propensity-matched “mNight” patients (age 43 ± 4.3, M/F 11/4, ISS 24.5 ± 2.5) presented during the shortest night period (10:00 pm-5:00 am). Serial blood samples were obtained (3 samples within the first 24 h and daily from days 1-7) from all patients. Thirty-two plasma inflammatory mediators were assayed. Two-way Analysis of Variance (ANOVA) was used to compare groups. Dynamic Network Analysis (DyNA) and Dynamic Bayesian Network (DyBN) inference were utilized to infer dynamic interrelationships among inflammatory mediators. Both total hospital and intensive care unit length of stay were significantly prolonged in the mNight group, despite a greater need for surgical interventions in mDay group. Circulating IL-17A was elevated significantly in the mNight group from 24 h – 7 days post-injury. Circulating MIP-1alpha, IL-7, IL-15, GM-CSF, and sST2 were elevated in the mDay group. DyNA demonstrated elevated network complexity in the mNight vs. the mDay group. DyBN suggested that cortisol and sST2 were central nodes upstream of TGF-beta1, chemokines, and Th17/protective mediators in both groups, with IL-6 being an additional downstream node in the mNight group only. Our results suggest that time of injury affects the clinical outcomes in severely injured patients in a manner associated with an altered systemic inflammation program, possibly implying a role for circadian variation in the response to traumatic injury.